Income Inequality, Education and Skill-Biased Technological Change - Xiao, Simin (Université d'Ottawa | University of Ottawa, 2019)
This paper provides an empirical analysis of the relationship among income inequality, education inequality and skill-biased technological change (SBTC thereafter). If education expansion reduces income inequality, SBTC increases it as it favors skilled (more educated) over unskilled labor. My paper develops a model that takes into consideration the skill-biased technological progress observed since 1990. My empirical results are consistent with the hypothesis that SBTC counteracts the education compression effect on income inequality to different extents over the past decades.